Real World Experience of Disease Activity in Patients With Rheumatoid Arthritis and Response to Treatment With Varios Biologic DMARDs - Boyadzhieva, Vladimira; Stoilov, Nikolay; Ivanova, Mariana; Petrova, Guenka; Stoilov, Rumen (Frontiers in Pharmacology, 2018)
The current study investigate the disease activity and effectiveness of treatment in patients with RA on biological disease modifying antirheumatic drugs (bDMARDs) in combination with a conventional synthetic DMARD (csDMARD) and determine whether or not the benefits of different therapies were sustained over a follow up period of one year. 124 patients were selected with a mean age 55.26±13,18SD years, meeting the 1987 ACR and /or ACR/ EULAR (2010) classification criteria for RA. Patients were arranged according to treatment regimens: Tocilizumab (TCL) - 30 patients, Certolizumab (CZP) – 16, Golimumab (GOL) – 22, Etanercept (ETN) 20, Adalimumab (ADA) 20, Rituximab (RTX) – 16. Disease activities was the primary concern. Independent joint assessor evaluated 28 joints on baseline, 6th and 12th month`s thereafter. C-reactive protein (CRP) was used to measure the inflammatory process. DAS28-CRP, CDAI and SDAI were calculated. On baseline all of the patients’ groups had severe disease activity (mean DAS28-CRP > 5.2, mean CDAI >22, mean SDAI >26. It was noted that, during the 6th month follow-up period all of the treatment groups significantly decreased DAS28-CRP, CDAI, SDAI and reach moderate disease activity. After 6th and 12th months of treatment all of the groups on bDMARDs had significantly lower disease activity. The GOL group reach remission only according to DAS28-CRP: 2.49 ± 0.76, and low disease activity as measured by CDAI: 6.78 ± 4.51 and SDAI 7.80 ± 5.67. The other 5 groups after 12 months reach the level of low disease activity according to the three activity parameters: DAS28-CRP ( TCL 3.07 ± 0.73, CZP 3.06 ± 0.65, ETN 2.85 ± 0.55, ADA 3.15 ± 0.82, RTX 2.90 ± 0.70), CDAI (TCL 9.80 ± 4.91, CZP - 9.33 ± 4.22, ETN 7.97 ± 3.80, ADA 10.00 ± 5.25, RTX 7.48 ± 2.99) and SDAI (TCL 10.45 ± 5.14, CZP 9.94 ± 4.43, ETN 9.03 ± 4.25, ADA 10.50 ± 5.61, RTX 8.08 ± 3.24). The therapy with different bDMARDs added to a csDMARD led to very similar results – a minimal disease activity and a state of remission in the GOL treatment group only as per DAS28-CRP.